2018
DOI: 10.1080/24750573.2018.1430714
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal epilepsy mimicking conversion disorder: a case report

Abstract: In children and adolescents, especially younger ones, recurrent abdominal pains may develop as a response to psychosocial stressors. They may be considered as functional and be one of the common reasons for clinical referrals. A rare cause of recurrent, organic abdominal pain is abdominal epilepsy. Abdominal epilepsy may be considered in differential diagnosis of patients that were thought to have functional complaints. In this case, a 16-year-old adolescent girl whose chief complaints included loss of conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Our patient has been diagnosed with dyspepsia. Öztürk, et al, reported a case of a 16-year old with abdominal epilepsy who was previously managed as conversion disorder [13]. Another child with abdominal epilepsy was misdiagnosed to have psychogenic pain [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient has been diagnosed with dyspepsia. Öztürk, et al, reported a case of a 16-year old with abdominal epilepsy who was previously managed as conversion disorder [13]. Another child with abdominal epilepsy was misdiagnosed to have psychogenic pain [14].…”
Section: Discussionmentioning
confidence: 99%
“…She was initially misdiagnosed with generalized anxiety and conversion disorders. After a neurological examination and electroencephalography, showing temporal lobe involvement, the patient was treated with the diagnosis of abdominal epilepsy (7).…”
Section: Discussionmentioning
confidence: 99%
“…Carbamazepine has been a cornerstone of therapy, demonstrating efficacy in symptom management and normalization of EEG findings. Recent reviews, advocate for the use of newer antiepileptic drugs (AEDs) with more favorable side effect profiles, enhancing patient outcomes in atypical epilepsy syndromes [20,21].…”
Section: Recent Advances and Literaturementioning
confidence: 99%